THE DAKWAH PARADIGM IN THE MILLENNIAL ERA - Ermeilinda Kartina Sari (Fakultas Agama Islam Universitas Islam As Syafi'iyah, 2020)
The paradigm in preaching in the millennial era provides the view that preaching in the millennial era generation who depends on technology and social media as a very important part in social networks considering that preaching is starting to develop well, then religion becomes a way of life in Islam and da'wah will be more interesting through social media which is also guided by the Islamic concept of rahmatan lilalamiin. One suggestion for that is the existence of Rohis as a religious activity in an extracurricular organization at school to be a complement in meeting the needs of religious education and shaping the character of students to be close to Allah swt. In addition, the steps taken in shaping students to become individuals who fear God in this millennial era, it is necessary to take other steps, including: (1) using social media so that students do not lose their identity, (2) regularizing the recitation in activities memorization of the Koran which aims to increase students' religious understanding.